Building Brand Awareness Through Modern Marketing Management - Lipu, Andi Tonra; Baharuddin, Andi (Journal of Economic Education and Entrepreneurship Studies, 2023)
This research aims to analyze the influence of content marketing on brand awareness using a simple linear regression method. The research sample consisted of 243 respondents who were randomly selected and had experience with brands that use content marketing. The research results show that content marketing has a significant positive influence on brand awareness, with a regression coefficient of 0.58 (p-value = 0.002). The regression model used can explain approximately 38% of the variation in brand awareness (R² = 0.38). These findings indicate that relevant and interesting content has an important role in increasing brand recognition among consumers. However, this research also shows that other factors, such as social media and influencer marketing, can contribute to increased brand awareness. Based on these results, it is recommended for companies to improve the quality and relevance of content, as well as utilize social media platforms and influencers to distribute content more effectively. Further research considering other variables that influence brand awareness is expected to provide more comprehensive insights in the context of digital marketing